Fermentation Characteristics and Bioactive Properties of Kombucha Senna alexandrina Mill. Leaves - Oktira Roka Aji; Diah Asta Putri; Alya Firli Refanza Putri; Nabela Dwi Wahyu Nurvi Fibriyanti; Siti Nurhasanah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Kombucha is a fermented beverage produced by a symbiotic culture of bacteria and yeast (SCOBY) and is widely recognized for its functional properties. This study investigated the fermentation characteristics, bioactive properties, antibacterial activity, ethanol content, and sensory attributes of kombucha produced from senna leaves (Senna alexandrina Mill.) during different fermentation periods (0, 4, 8, and 12 days). Physicochemical parameters including pH, optical density, SCOBY biomass, reducing sugar, and total titratable acidity were monitored, while bioactive properties were evaluated through total phenolic content and antioxidant activity (IC50). Antibacterial activity against Escherichia coli, ethanol content, and sensory characteristics were also analyzed. The results showed that fermentation significantly decreased pH while increasing total titratable acidity, optical density, and SCOBY biomass, indicating active microbial metabolism. Total phenolic content increased during fermentation from 96.80 to 119.56 µg GAE/mL, accompanied by a substantial improvement in antioxidant activity as indicated by decreasing IC50 values. Antibacterial activity against E. coli was absent in the unfermented sample but emerged after fermentation. Ethanol concentration increased gradually but remained very low (0.0141% at day 12), well below regulatory limits for non-alcoholic and halal beverages. Sensory evaluation showed that fermentation time influenced taste and aroma, while color remained relatively stable. Overall, the findings demonstrate that senna leaves can serve as a suitable herbal substrate for kombucha fermentation and contribute to the development of functional fermented beverages with enhanced bioactive properties.